PKM Pelatihan dan Pendampingan Produksi Minyak Gosok Alami Pala di Pondok Pesantren dan Panti Asuhan - Sumantri Abdullah, Surya; Antasionasti, Irma; Ahmad, Musfirah; Jayanto, Imam (Yayasan Bina Lentera Insan, 2025)
Herbal rubbing oil is a widely used traditional remedy for relieving muscle pain, improving blood circulation, and promoting relaxation. Nutmeg (Myristica fragrans) contains several bioactive compounds such as myristicin, safrole, eugenol, and elemicin, which possess analgesic and anti-inflammatory properties, making it suitable for development into a natural rubbing oil product. However, the utilization of nutmeg oil as an economically valuable herbal product remains underdeveloped, particularly in Islamic boarding schools and orphanages, where practical skills and entrepreneurial knowledge are highly needed. This Community Service Program (PKM) aimed to provide training and assistance in producing nutmeg-based rubbing oil through educational sessions, demonstrations, and hands-on practice. The results indicate a significant improvement in participants’ knowledge regarding the benefits of nutmeg and the safe use of herbal remedies, as well as an enhancement in technical skills related to production, packaging, and understanding product economic value. Participants successfully produced stable nutmeg rubbing oil with a distinct aromatic profile. The program positively contributed to improving health independence and promoting micro-entrepreneurship based on natural herbal products. This initiative demonstrates strong potential to be replicated in similar institutions as a model for local resource–based economic empowerment.